The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.tvjl.2014.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of autologous bone marrow cells into the injured cranial cruciate ligament in dogs

Abstract: Current research indicates that exogenous stem cells may accelerate reparative processes in joint disease but, no previous studies have evaluated whether bone marrow cells (BMCs) target the injured cranial cruciate ligament (CCL) in dogs. The objective of this study was to investigate engraftment of BMCs following intra-articular injection in dogs with spontaneous CCL injury. Autologous PKH26-labelled BMCs were injected into the stifle joint of eight client-owned dogs with CCL rupture. The effects of PKH26 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…The clinical application of MSC-based therapy in veterinary medicine comprises of multiple target diseases, with the vast majority being focused on musculoskeletal conditions such as osteoarthritis (8,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), cruciate ligament disease (9,(35)(36)(37)(38), hip dysplasia (39), bone fractures and lesions (40,41), muscle tears (42,43) and tendinopathies (44,45). Canine clinical studies have also shown promising results for the treatment of diseases of the gastro-intestinal tract (46)(47)(48), central nervous system (49)(50)(51)(52)(53), cardiovascular system (54,55), cutaneous (56)(57)(58)(59) and ocular conditions (60)(61)(62)(63), resulting in encouraging safety and efficacy data (Figure 2).…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…The clinical application of MSC-based therapy in veterinary medicine comprises of multiple target diseases, with the vast majority being focused on musculoskeletal conditions such as osteoarthritis (8,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), cruciate ligament disease (9,(35)(36)(37)(38), hip dysplasia (39), bone fractures and lesions (40,41), muscle tears (42,43) and tendinopathies (44,45). Canine clinical studies have also shown promising results for the treatment of diseases of the gastro-intestinal tract (46)(47)(48), central nervous system (49)(50)(51)(52)(53), cardiovascular system (54,55), cutaneous (56)(57)(58)(59) and ocular conditions (60)(61)(62)(63), resulting in encouraging safety and efficacy data (Figure 2).…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…It was demonstrated that the level of post-operative lameness and pain after single intra-articular injection of allogeneic BMMSC could be a valuable alternative to 1 month course of oral administration of non-steroidal anti-inflammatory drugs (NSAIDs) in dogs requiring tibial plateau leveling osteotomy (TPLO) (178). It was shown that intraarticularly injected autologous BMMSCs engraft to the site of the injured cranial crucial ligament (179) and have an anti-inflammatory effect. Post-operatively intraarticular or IV injection of autologous MSC in dogs with the same condition resulted in a decreased level of CD8+ Tcells, decreased serum and synovia CRP, and decreased synovial IFN-γ levels that persisted over 8 weeks after BMMSC injection (180).…”
Section: Tendons and Ligaments Diseasesmentioning
confidence: 99%
“…Even though insight into the mechanisms of senescence in human medicine has evolved dramatically 18 , knowledge about replicative senescence of canine ( Canis lupus familiaris ) MSCs is still very scarce 1921 . Therapeutic use of stem cells in veterinary medicine has not yet progressed beyond pioneering work 22,23 . Correspondingly, there is a great interest in this field 24 , both for the importance of dogs as a model organism for human diseases in pre-clinical studies and for the relevance of dogs as a companion animal.…”
Section: Introductionmentioning
confidence: 99%